Dealing with Emotions in “Inside Out” Movie: Moral Value Analysis - Ni Made Verayanti Utami; Sinarawerdhi, I Gst Ayu Intan (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This study is about Analysis of Moral Values in the Inside Out Film, examining the types of moral values reflected by the characters. The information is obtained from conversations and moments from the film Inside Out which contains moral lessons. To find the moral principles in the Inside Out film, the data were examined using the theory proposed by Linda and Eyre (1993). In this study, the method used to collect data is the observational method. To identify and evaluate the data, note taking technique was used to observe the data. The data were examined qualitatively, then reported descriptively. The purpose of this study was to find the moral values contained in the film Inside Out, from the results of this study found 10 types of moral values contained in it, namely honesty, courage, self-reliance and potential, fidelity and chastity, loyalty and dependability, respect, love and affection, unselfishness and sensitivity, kindness and friendliness, justice and mercy. Of the 10 moral values found, 3 of them that stand out the most in this film are the moral values of loyalty and dependability, respect and unselfishness and sensitivity.